Main factors controlling hydrocarbon accumulation in the Northwestern Sichuan Basin - Xiao, Hang; Xu, Fanghao; Fu, Xiaodong; Li, Wenzheng; Chen, Cong; Zhang, Jianyong; Wang, Yajie; Zhou, Kuan (Frontiers in Earth Science, 2022)
The basin-mountain transition regions of foreland basins are hot spots for hydrocarbon exploration worldwide, while the complex geological features and hydrocarbon accumulation rules make hydrocarbon exploration very difficult. The Northwestern Sichuan Basin is a typical case where the unclear distribution rules restrict the further exploration of natural gas. In this study, geochemistry and seismic profile data were comprehensively used to reveal the main factors controlling hydrocarbon accumulation in the Northwestern Sichuan Basin. The Lower Cambrian and the Upper- Middle Permian source rocks have different carbon isotope compositions, indicating that they have different kerogen types, sapropelic kerogen for the Lower Cambrian source rocks, mixed kerogen for the Middle Permian source rocks and humic kerogen for the Upper Permian source rocks. The Northwestern Sichuan Basin can be divided into the unfaulted belt, the thrust front belt and the thrust nappe belt. The thrust nappe belt develops many large thrust faults, and the natural gas there mainly originates from the Lower Cambrian source rocks. However, due to different denudation of regional caprocks, hydrocarbons in the area adjacent to the Longmen Mountain fold-and-thrust system were destroyed, while in the area adjacent to the thrust front belt, they had good preservation conditions. The thrust front belt and the unfaulted belt develop a few or few thrust faults, and the natural gas there mainly originates from the Upper-Middle Permian source rocks and has good preservation conditions due to no denudation of regional caprocks. The distribution of thrust faults controls the natural gas origins in different areas, and the preservation conditions determine whether the gas reservoirs can survive to the present. These conclusions can provide guidance for natural gas exploration in the Northwestern Sichuan Basin and other basin-mountain transition regions in foreland basins worldwide.